Paesaggi rurali in Sardegna: ‘interferenze’ progettuali nella regione storica della Marmilla - Atzeni, Carlo; Mocci, Silvia (Scienze del Territorio, 2017)
The settlement system of Marmilla, historic hill area of central Sardinia, has endured for decades with increasing difficulties to depopulation and crisis of belonging of communities. The historic balance that characterized the mutual rooting between communities and places is questioned and sets questions on the meaning of living in these places and on the sense of the redevelopment of historic and traditional rural heritage. The community initiatives adopted by Regione Sardegna for the redevelopment of these areas point at the definition of quality projects for networks of small towns with cultural, territorial, economic common characters. In accordance with such objectives, the project of architectures and public spaces tries to share principles, targets, tools, languages, techniques and materials with in order to give form to a system strategy at the territorial scale. Marmilla already holds design micro-actions that contribute to create quality spaces transforming the territory into an extraordinary place for the experimentation of the construction and the continuous renewal of local specificities. the architecture project becomes, then, an instrument to measure the quality of places and their capability to go beyond the test of time adapting itself and reformulating their space-time, value, cultural coordinates: in other words, their resilience capability.